Developing Critical And Creative Thinking-Based Islamic Religious Education Learning Designs Using Discovery Learning Strategies Through Saintificate Approaches - Zumzianah; Wahab (IJGIE (International Journal of Graduate of Islamic Education), 2023)
This research aims to describe and analyze the development of Islamic Religious Education learning design based on critical and creative thinking with a scientific approach to discovery learning strategies. This research method uses qualitative research with descriptive research types. The primary data sources in the study were Islamic Religious Education teachers, students, and school principals. Secondary data sources are in the form of books, research journals, and documentation. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use data reduction, analysis, interpretation, and triangulation. The results of this study state that the learning process of jurisprudence still uses a lot of methods that are less interesting because it is too monotonous to only use one method, namely the lecture method, without being balanced with other methods, so the learning atmosphere is less attractive, looks pretty dull, without the support of exciting media and facilities. as did MTsN teachers, and State MA teachers.